Modelling the association between core and discretionary energy intake in adults with and without obesity - Fong, M; Li, A; Hill, AJ; Cunich, M; Skilton, MR; Madigan, CD; Caterson, ID (MDPI, 2019)
BACKGROUND: Many dietary recommendations for weight control rely on the assumption that greater core food intake will displace intake of energy-dense discretionary foods and beverages. However, there is little evidence to support these assumptions. This study examined the naturalistic relationship between daily core and discretionary energy intake, and with discretionary food and discretionary beverage intake, separately. The impact of weight status on these associations was also examined. METHOD: One hundred participants completed a four-day (non-consecutive) estimated food diary. Discretionary foods and beverages were identified by reference to the Australian Dietary Guidelines. Non-discretionary items were considered core items. Simultaneous-equation random effects models using disaggregated dietary data controlling for sociodemographic variables were used to determine the association between various dietary components. RESULT: Core energy intake correlated negatively with discretionary energy intake (cross-equation correlation, ρ = -0.49 (95% CI: -0.57, -0.39)). Its correlation with discretionary foods (-0.47 (-0.56, -0.37)) was stronger than that with discretionary beverages (-0.19 (-0.30, -0.07)) The correlation between core energy intake and discretionary energy intake was significantly stronger in participants who did not have obesity (-0.67 (-0.71, -0.50)) than those with obesity (-0.32 (-0.46, -0.17)) (p = 0.0002). CONCLUSIONS: Core and discretionary energy intake share an inverse and potentially bidirectional, relationship that appears to be stronger with discretionary foods than discretionary beverages. These relationships were significantly weaker in participants with obesity which may indicate less precise dietary compensation in these individuals. While strategies that promote greater intake of core foods may assist with weight maintenance in individuals of healthy weight, its impact in individuals with obesity may be limited. These strategies should be accompanied by direct messages to reduce commensurately the intake of discretionary items, with special attention paid to discretionary beverage consumption.